21-Hydroxypregnane 21-O-malonylation, a crucial step in cardenolide biosynthesis, can be achieved by substrate-promiscuous BAHD-type phenolic glucoside malonyltransferases from Arabidopsis thaliana and homolog proteins from Digitalis lanata. (July 2021) - Tropper, Marina; Höhn, Stephanie; Wolf, Laura-Sophie; Fritsch, Julia; Kastner-Detter, Nina; Rieck, Christoph; Munkert, Jennifer; Meitinger, Nadine; Lanig, Harald; Kreis, Wolfgang
Abstract: Three putative 21-hydroxypregnane 21- O -malonyltransferases (21MaT) from Digitalis lanata were partially purified. Two of them were supposed to be BAHD-type enzymes. We were unable to purify them in quantities necessary for reliable sequencing. We identified two genes in A. thaliana coding for substrate-promiscuous BAHD-type phenolic glucoside malonyltransferases ( At PMaT1, At PMaT2) and docked various 21-hydroxypregnanes into the substrate-binding site of a homology model built on the BAHD template 2XR7 ( Nt MaT1 from N. tabacum ). Recombinant forms of Atpmat1 and Atpmat2 were expressed in E. coli and the recombinant enzymes characterized with regard to their substrate preferences. They were shown to malonylate various 21-hydroxypregnanes. The Atpmat1 sequence was used to identify candidate genes in Digitalis lanata ( Dlmat1 to Dlmat4 ). Dlmat1 and Dlmat2 were also expressed in E. coli and shown to possess 21-hydroxypregnane 21- O -malonyltransferase activity. Graphical abstract: Heterologously expressed BAHD-like malonyltransferases from Digitalis lanata (A) and Arabidopsis thaliana (B) catalyze the 21- O -malonylation of 21-hydroxypregnanes. Molecular modeling and docking helped evaluating and predicting substrate acceptance. Image 1 Highlights: BAHD-like malonyltransferases were partially purified from Digitalis lanata and A. thaliana . Molecular modeling/docking helped to evaluate potential substrates for BAHD-like enzymes. BAHD-like malonyltransferase cDNAs were isolated from D. lanata and A. thaliana . Recombinant forms of various BAHD-like enzymes were produced in E. coli . 21-Hydroxypregnanes can be 21-O-malonylated by several BAHD-like malonyltransferases.